Are cosmetics a significant source of PFAS in Europe? product inventories, chemical characterization and emission estimates. Issue 10 (12th August 2022) - Pütz, Kerstin Winkens; Namazkar, Shahla; Plassmann, Merle; Benskin, Jonathan P.
Abstract : Estimates of per- and polyfluoroalkyl substance (PFAS) emission from the use of cosmetics in Europe. Abstract : In this study, emission of per- and polyfluoroalkyl substances (PFAS) from the use of cosmetics in the European Economic Area (EEA; not including Lichtenstein and Iceland) was estimated for the first time. Using the European Commission database for information on cosmetic substances and ingredients (CosIng) ∼170 structures containing at least –CF2 – or –CF3 were identified as ingredients in cosmetics on the European market. These structures were then cross referenced against the Cosmetic Database "CosmEthics" to identify PFAS-containing products. Among these products, polytetrafluoroethylene (PTFE) and C9-15 fluoroalcohol phosphate were the most frequently listed PFAS ingredients. Thereafter, a sample of 45 cosmetics spanning 5 product categories was purchased in Sweden and characterized for total fluorine (TF), extractable organofluorine (EOF), and target PFAS. Using measured concentrations, the share of PFAS-containing products in each product category, sales data from Cosmetics Europe, as well as other parameters and assumptions, the annual emission of PFAS from cosmetics after use was estimated. Annual EEA-wide TF and EOF-based emissions ranged from ∼17–38 000 kg F per year and 37–5100 kg F per year, respectively, representing combined emission to wastewater and solid waste (low to high emission scenario). Sum perfluoroalkyl carboxylic acid (PFCA) emissions were considerably lower (21 kg ∑PFCAs per year; high scenario). While TF- and EOF-based emissions are significant, they are considerably lower than estimates of TF emission from washing of PFAS-coated textiles in the EU. This work provides the first estimate of PFAS emissions from cosmetics and highlights the importance of using a multi-platform analytical approach for PFAS emission estimates.